Empreendedores: sucessos e insucessos das micro e pequenas empresas do Vale do São Francisco - Oliveira, Deranor Gomes de (2010)
This dissertation describes the attributions of causality for the success or the failure of ten entrepreneurs, owners of micro and small enterprises in the Sao Francisco Valley more specifically in Juazeiro (BA), by using narratives of their life and business story. In order to do this, an exploratory research was conducted through in-depth interviews. The data processing used the technique of content analysis supported by software ATLAS/ti. Theoretical and empiric studies on an entrepreneur s competencies and psychological traits found in the scholarly literature and the results from the research helped identify the dimensions related to the attributions of causality in situations of achievement of entrepreneurs. The results show that the importance of socio-environmental aspects, the difficulty of the task (and the facilitators found in the external environment), as well as the entrepreneurs personal characteristics cannot be underestimated, because of its relevance. The results lead to the following final considerations: an external environment prone to the development of the entrepreneurship does not guarantee alone the success of the business. So success is achieved, when aspects related to the entrepreneur s personal characteristics and cognitive aspects are present, associated to a favourable scene. Successful entrepreneurs valued internal causes, whereas unsuccessful entrepreneurs blamed difficulties found in the external environment for their failure.